Intensity of Erosive Processes at Channel Banks of the Upper Paraná River, Porto Rico town Area, Parana State (Brazil) - DOI 10.5216/bgg.v19i1.15294 - P.C, Rocha; E.E, Souza Filho; O.V.Q, Fernandes (Boletim Goiano de Geografia, 2011)
.